PEMBELAJARAN BAHASA ARAB SEBAGAI BAHASA ASING TERHADAP ANAK USIA DINI - Imas Jihan Syah (Universitas Islam Lamongan, 2018)
Foreign language learning Including Arabic is much more achievable when embedded in early childhood. Given language is habituation. The scope of Arabic learning includes: linguistic elements, composed of grammar ( qawaidul lughoh ) ,vocabulary, pronunciation and spelling ( aswat arabiyah ), language skills, is listening ( istima'), speaking ( kalam ), reading ( qiro'ah ), and writing ( kitabah ) and cultural aspect contained in oral and written text. In Arabic language learning is expected to encourage, guide, develop and nurture the ability of students and grow a positive attitude toward Arabic language both receptive and productive. Especially in learning Arabic for early childhood is the beginning of preparation for children to have knowledge, experience and skills to make children more ready and have a global insight. Considering Arabic is the language of worship, introduction of science, especially the Islamic treasures and has become the culture and civilization of Islam. And the civilization should not be forced.